The Impact of Age Difference on the Efficacy and Safety of COVID-19 Vaccines: A Systematic Review and Meta-Analysis - Wang, Jiting; Tong, Yue; Li, Duo; Li, Jun; Li, Yaling (Frontiers in Immunology, 2021)
Objective: This meta analysis compare the efficacy and safety of 5 kinds of COVID-19 vaccines in different age (young adults and older adults), aiming to analyze the difference of adverse events (AEs) rate and virus geometric mean titre (GMT) value between young and older people, and to find a specific law and explore the causes of this law through meta-analysis. Method: Meta-analysis was used to analyze the 5 eligible literatures.The modified Jadad Scoring Scale was used to evaluate the quality of eligible literature methodology with a score system of 1 to 7.Primary endpoints of effectiveness index was GMT. Primary endpoint of safety index were the incidence of local AEs and systemic AEs.Revman5 software was used to map the risk of publication bias, and Egger’s test was used to analyze publication bias. Results: The GMT values of young adults were higher than older adults (SMD = 1.40, 95% CI (0.77, 2.02), P<0.01).Higher incidence of local and systemic AEs in young people than in the elderly (OR = 1.10, 95% CI (1.08, 1.12), P<0.01; OR = 1.18, 95% CI (1.14, 1.22), P<0.01). Conclusion: The immune effect of young people after being vaccinated with COVID-19 vaccines is better than that of the elderly, but the safety was worse than that of old people, the most common AEs were fever, rash and local muscle pain, which are tolerable for young people. As the AEs of the elderly are lower, they can also be vaccinated safely, the reason why the GMTs of the elderly were lower being related to human Immunosenescence. The vaccine tolerance of people of different ages needs to be studied continuously.